Gynecologists Awareness Regarding Periodontal Disease and Adverse Pregnancy Out- come - O. Mahfoud, Salma; Elmoghrbi, Marie; B. Al Ghazal, Logien; K. Al magrahi, Warda; M. El Barasi, Ame-Asaad; Bazina, Manal (Libyan Journal of Dentistry, 2020)
Pregnancy adverse outcomes are known as preterm birth (PTB) and low birth weight (LBW). Up to date the exact mechanism by which adverse outcomes occur is not known. One of the conditions that is reported by the literature could be associated or linked to it is periodontal disease (PD). Gynecologists are the primary health care providers, and are in constant contact with pregnant women. It has been recommended that gynecologist should have an acceptable level of knowledge regarding periodontal disease and adverse pregnancy outcome. Objective: To assess the level of awareness among gynecologists practicing in Benghazi, regarding to the association between periodontal disease and adverse pregnancy outcomes. Methods: Cross-sectional interview structured question- naire study, was conducted to assess the level of awareness among gynecologists practicing in Benghazi city about the effect of chronic periodontal disease (PD) on pregnancy outcome. One hundred and seven Gynecologists par- ticipated in this study. The questionnaire consisted of 16 questions that assessed knowledge and attitude among the participated gynecologists. Results: The current study showed that while the majority of gynecologists knew about hormonal effects on the periodontium, and the common signs and symptoms of PD, only 20.6% were aware about the importance of a regular dental check-up during pregnancy. About 22.4% of them considered that PD could be a risk factor for adverse pregnancy outcome. We found that 87% of the gynecologists show an agreement that periodontal treatment should be an essential part of prenatal care program. Conclusions: this study con- cludes despite high level of awareness among gynecologist, very few refer or advise their patients to receive dental treatment during pregnancy. We suggest that continuing medical and dental education programs and intercom- munication between healthcare providers may provide a better-quality healthcare service to the community.